2021
DOI: 10.3389/fcell.2021.771773
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Self-Assembled Patterns Maintain the Pluripotency and Promote the Hemopoietic Potential of Human Embryonic Stem Cells

Abstract: The generation of blood cells in a significant amount for clinical uses is still challenging. Human pluripotent stem cells-derived hemopoietic cells (hPSC-HCs) are a promising cell source to generate blood cells. Previously, it has been shown that the attached substrates are crucial in the maintenance or differentiation of hPSCs. In this study, a new family of artificial extracellular matrix (ECM) called colloidal self-assembled patterns (cSAPs: #1–#5) was used for the expansion of mouse and human PSCs. The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…17 Each has a unique and defined surface physicochemical property, including surface topography, ma- terial chemistry, and wettability. These surface properties have been previously described, 18,25,26 highlighting the capability of the cSAPs to regulate cell adhesion and cytoskeletal dynamics. 27 Our previous studies have also demonstrated that cSAPs can elicit diverse biological effects on mammalian cells, with some promoting stem cell differentiation and others enhancing cell reprogramming efficiency.…”
Section: Discussionmentioning
confidence: 77%
“…17 Each has a unique and defined surface physicochemical property, including surface topography, ma- terial chemistry, and wettability. These surface properties have been previously described, 18,25,26 highlighting the capability of the cSAPs to regulate cell adhesion and cytoskeletal dynamics. 27 Our previous studies have also demonstrated that cSAPs can elicit diverse biological effects on mammalian cells, with some promoting stem cell differentiation and others enhancing cell reprogramming efficiency.…”
Section: Discussionmentioning
confidence: 77%
“…JAK/STAT signaling pathway is a central node that regulates cellular processes through signal transduction 23 . It responds to tissue turnover and regeneration via regulating stem cells, including hematopoietic stem cells 24 , embryonic stem cells 25 , as well as ISCs 26 . It is also a maintainer for cancer stem cells and promoter for multiple cancers, such as colorectal cancer 27 .…”
Section: Discussionmentioning
confidence: 99%